Science and religion as languages: using the "language" metaphor to understand science, religion, and their relationship - Lee, AH (2023)
In the field of science and religion, there is a need for a model that represents the dynamic science-religion interface without curtailing its rich complexities. This thesis proposes the “language” metaphor to describe and explore science, religion, and their relationship and sets out to assess its potential in this respect by considering its application in six areas of interest—namely, the definition of language; its changes over time; variations within languages; the relation between language and worldview; the relation of language, identity and power; and the significance of bilingualism and the role of translation.